The Form of Life of the Contemporary Spiritual Pilgrimage: the Case of Santiago de Compostela - Ponzo, Jenny; Chiais, Eleonora (E|C, 2022)
This essay focuses on the paper and digital literature about the Camino de Santiago de Compostela (particularly on tourist guides and travel stories) to explore today's practice of pilgrimage and how it can take a spiritual rather than religious form. This kind of pilgrimage is narrated as an inner quest free from religious faith and traditional devotion. The reflection compares the form of life of the pilgrimage to Santiago with the form of life which characterizes the tourist experience in general ( as it is defined by Brucculeri). It then takes into consideration the pragmatic and narratological dimension of the spiritual pilgrimage and identifies three main phases (the first consists in the acquisition of a competence through the use of "programmer" texts, the second in the personalization of the narrative program, when the subject takes in charge the standardized scheme, and the third in the narration of the journey). This type of pilgrimage is characterized by an object of value which is initially undefined and progressively becomes clear as the pilgrim advances. It is also characterized by dynamics similar to those identified by Caillois concerning the game. In particular, the category of mimicry is relevant. The pilgrim has their own uniform, which is well recognizable, but starting from some standard elements they can build a different path and a different character depending on their values and tastes: from this perspective, the pilgrim constitutes a thematic role that is embodied in different figurative roles.